Carbon emissions trading and equity in international agreements - Francesco Bosello; Roberto Roson (Fondazione Eni Enrico Mattei (FEEM), 1999)
An integrated assessment model is used to simulate the introduction of various emissions trading schemes based on the Kyoto protocol on the reduction of greenhouse emissions. The implications of the various systems in terms of income distribution are illustrated, and it is claimed that the issue of equity should not be regarded as independent of the issue of market efficiency. In particular, in this paper it is shown that (1) changes produced on an equity index by the imposition of emission constraints (by country) are not significantly higher than those obtained by the subsequent introduction of a market mechanism, and (2) that the different market regimes which could be adopted have quite different distributional implications. These results are interpreted as a direct consequence of the fact that a competitive market equilibrium is equivalent to a centralised social welfare maximisation in which the function to be maximised, however, normally differs from the social function used to define equity objectives.
Keywords: C5; F1; F4; 330; Equity/Efficiency; Emissions Trading; Banking; Flexibility mechanisms; International environmental agreements; Kyoto; Integrated Assessment Modelling; Emissionshandel; Treibhausgas-Emissionen; Umweltabkommen; Wirtschaftliche Effizienz; Verteilungsgerechtigkeit; Soziale Wohlfahrtsfunktion; Simulation; Theorie; Welt